Indonesian Case: Good Corporate Governance, Company Size, Taxes, and Transfer Pricing - Mamay Komarudin; Hari Gursida; Yohanes Indrayono (Journal of Business and Management Review, 2022)
ge companies have tax deficiencies and will inevitably use more aggressive transfer pricing manipulations. GCG and company size can influence company decisions in making transfer pricing. This research is fundamental to developing a model and conceptual coding and causality of transfer pricing practices while testing the influence of motivational factors on transfer pricing. The problem in this study is that Good Corporate Governance (GCG) strengthens the effect of taxes on transfer pricing in multinational companies, and apakah of company size weakens the influence of taxes on transfer pricing in multinational companies. This type of research is explanatory research using data from 2010-2020. The type of data used in this study is secondary data in the form of financial statements of manufacturing companies published by the Indonesia Stock Exchange obtained from the IDX Fact Book and OJS. The population in this study, namely all multinational companies in the manufacturing and services sector listed on the KOMPAS 100 index on the Indonesia Stock Exchange (IDX), amounted to 100 companies. The sample was based on purposive sampling, so 48 companies were selected. The data collection technique in this study is documentation. This study used a simultaneous equation model for panel data analysis and the Granger causality test. Based on the results of the study, it can be concluded that 1) The role of GCG in strengthening the influence of taxes on transfer pricing is significantly indicated by the p-value test t variable moderation GCG *tax of 0.000 < 0.05; 2) The role of company size weakens the effect of taxes on transfer pricing significantly, indicated by the p-value test t variable moderation size *tax of 0.000 < 0.05.